2017
DOI: 10.5114/aoms.2016.58596
|View full text |Cite
|
Sign up to set email alerts
|

Right- and left-sided colon cancer – clinical and pathological differences of the disease entity in one organ

Abstract: IntroductionSome researchers suggest that cancers located in the right vs. the left side of the colon are different and they can be regarded as distinct disease entities. The aim of this study was to analyze differences in clinical, epidemiological and pathological features of patients with right-sided (RCC) and left-sided (LCC) colon cancer.Material and methodsOne thousand two hundred and twenty-four patients were operated on due to colorectal cancer. A group of 477 patients (254 women, mean age 65.5 ±11 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
92
1
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 15 publications
15
92
1
7
Order By: Relevance
“…Furthermore, the number of HLNs was higher in the RCC group than in the LCC group (23.8 vs. 19.2, p = 0.003). Mik et al also reported that the total number of HLNs was higher in the RCC group (11.7 vs, 8.3 ; p = 0.0001), and these results are similar to our own findings [32]. The reason for this was due to the differences in the resected area, depending on the tumor location.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the number of HLNs was higher in the RCC group than in the LCC group (23.8 vs. 19.2, p = 0.003). Mik et al also reported that the total number of HLNs was higher in the RCC group (11.7 vs, 8.3 ; p = 0.0001), and these results are similar to our own findings [32]. The reason for this was due to the differences in the resected area, depending on the tumor location.…”
Section: Discussionsupporting
confidence: 91%
“…Proximal and distal colon tumors are suggested to be clinically, pathologically and transcriptionally distinct within CRC [4,61]. Multi-omics studies aimed at identifying differences between RSCC and LSCC have often targeted a direct comparison between the two tumor sides (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Right-sided colon cancers (RSCC or proximal tumors) occur in the cecum, ascending colon, hepatic flexure and/ or transverse colon, while left-sided colon cancers (LSCC or distal tumors) arise in the splenic flexure, descending colon, and/or sigmoid colon. This distinction has been observed at physiological, molecular and therapeutic levels for RSCC and LSCC [4]. For example, from the perspective of disease management, National Comprehensive Cancer Network (NCCN) Clinical Practice Guidelines in Oncology outline differences in therapeutic sensitivities of targeted drugs differ between sites in CRC for e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The left side of the colon derives from the embryonic hindgut, whereas its right side derives from the midgut. Some authors therefore postulate that leftand right-sided colon cancers should be viewed as two distinct disease entities [6,7]. In advanced neoplasia of the colon, distal tumors are characterized by their polypoid structure and are easier to detect in colonoscopy compared with flat proximal tumors.…”
Section: Introductionmentioning
confidence: 99%